2010
DOI: 10.1063/1.3463037
|View full text |Cite
|
Sign up to set email alerts
|

Depleted-heterojunction colloidal quantum dot photovoltaics employing low-cost electrical contacts

Abstract: With an aim to reduce the cost of depleted-heterojunction colloidal quantum dot solar cells, we describe herein a strategy that replaces costly Au with a low-cost Ni-based Ohmic contact. The resultant devices achieve 3.5% Air Mass 1.5 power conversion efficiency. Only by incorporating a 1.2-nm-thick LiF layer between the PbS quantum dot film and Ni, we were able to prevent undesired reactions and degradation at the metal-semiconductor interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 12 publications
2
21
0
Order By: Relevance
“…This can generally be seen via chemical analysis of the interface using XPS. 20 If the dielectric film is thermodynamically favored but deposited by chemical means such as chemical vapor deposition (CVD), then reaction kinetics can play a major role in interface formation. This can lead to compositions that are 16 This has also been observed for HfO 2 deposited onto Si by means of CVD.…”
Section: Resultsmentioning
confidence: 99%
“…This can generally be seen via chemical analysis of the interface using XPS. 20 If the dielectric film is thermodynamically favored but deposited by chemical means such as chemical vapor deposition (CVD), then reaction kinetics can play a major role in interface formation. This can lead to compositions that are 16 This has also been observed for HfO 2 deposited onto Si by means of CVD.…”
Section: Resultsmentioning
confidence: 99%
“…[3,10,11,13,24] Both effects make these materials suitable for the harvesting of solar light and its transformation into chemical/electrical energy, and hence for implementation in photocatalysis, photovoltaics, optoelectronics, biological labeling, and other areas. [13,14,[25][26][27] The noble metals Au and Ag coupled with TiO 2 , ZnO, CdSe, CdS, and PbS have been widely used for such applications. [13,[26][27][28][29][30][31] Literature study revealed that these materials broadly follow two types of carrier-transformation pathways on visible-light irradiation.…”
mentioning
confidence: 99%
“…[13,14,[25][26][27] The noble metals Au and Ag coupled with TiO 2 , ZnO, CdSe, CdS, and PbS have been widely used for such applications. [13,[26][27][28][29][30][31] Literature study revealed that these materials broadly follow two types of carrier-transformation pathways on visible-light irradiation. In one case, the hot electron generated from the surface plasmon of the noble metal is transferred to the semiconductor, and in the other case, the photogenerated electron moves from the semiconductor to metal.…”
mentioning
confidence: 99%
“…10, 11, 13, 24 Both effects make these materials suitable for the harvesting of solar light and its transformation into chemical/electrical energy, and hence for implementation in photocatalysis, photovoltaics, optoelectronics, biological labeling, and other areas 13. 14, 2527 The noble metals Au and Ag coupled with TiO 2 , ZnO, CdSe, CdS, and PbS have been widely used for such applications 13. 2631 Literature study revealed that these materials broadly follow two types of carrier‐transformation pathways on visible‐light irradiation.…”
mentioning
confidence: 99%